2013 29th Southern Biomedical Engineering Conference 2013
DOI: 10.1109/sbec.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution at the Bone-cement Interface Changes during Kyphoplasty Rehabilitation

Abstract: Abstract-Balloon Kyphoplasty uses an inflatable bone tamp and cement augmentation to repair vertebral compression fractures. A recent clinical study observed a 78% re-collapse rate in patients showing a radiolucent phenomenon at the bonecement interface following Kyphoplasty. Two experimental studies showed significant height loss following Balloon Kyphoplasty under cyclical loads. The present study investigates the alteration in load angle corresponding to this height loss and its effect on load transfer to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These models have been further utilised to study the micromechanics of the bone cement interface, which is an important feature for augmentation outcomes (Purcell et al, 2014(Purcell et al, , 2013Zhao et al, 2012). Many of these studies utilise an aluminium based open cell structure, which have been found to exhibit favourable properties for the study of cement injection micromechanics in terms of damage evolution and distribution (Guillén et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These models have been further utilised to study the micromechanics of the bone cement interface, which is an important feature for augmentation outcomes (Purcell et al, 2014(Purcell et al, , 2013Zhao et al, 2012). Many of these studies utilise an aluminium based open cell structure, which have been found to exhibit favourable properties for the study of cement injection micromechanics in terms of damage evolution and distribution (Guillén et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge only 2 other kyphoplasty models have explicitly represented the interface as a layer of elements surrounding the cement with an intermediary modulus assigned. [35][36][37][38] The majority of macroscale kyphoplasty simulations instead assume an instantaneous transition of elastic properties from bone to cement via shared node bonding of the domains. 39-43 These assumptions would not have been deemed unreasonable before the more recent in vivo observations of bone-cement interface separation.…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of the kyphoplasty treatment is the balloon expansion process, since in addition to decompressing the collapsed vertebra it also creates a cavity surrounded by a periphery of compacted trabeculae displaced by the balloon in the trabecular centrum. [9][10][11] In-vitro studies on human vertebra have found that this zone of compacted trabeculae can impede the subsequent infiltration of injected bone cement, which is necessary for effective load transfer and structure stabilization. 12,13 The adverse consequences of this effect were first reported in vivo by Mazwi et al, when a patient presented with back pain two months after kyphoplasty intervention.…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies have postulated that this re-collapse mechanism could be related to the compaction of trabecular bone during the balloon inflation process, thereby reducing the permeability. [10][11][12]19,20 A hypothesised factor in these recollapse events has been the clear difference in interdigitation patterns, with a 29.5% occurrence of a lumped cement mass in kyphoplasty cases compared to just 4.6% in vertebroplasty cases. 21 A significant proportion of these adverse events have been reported during the first 60 days following the original intervention.…”
Section: Introductionmentioning
confidence: 99%